Osteoporosis Remains Constant in Patients with Hemophilia—Long-Term Course in Consideration of Comorbidities - Strauss, Anna C.; Muellejans, Pius; Koob, Sebastian; Goldmann, Georg; Pennekamp, Peter H.; Wallny, Thomas A.; Oldenburg, Johannes; Strauss, Andreas C. (Hämostaseologie, 2023)
Introduction Patients with hemophilia (PWHs) suffer from an increased risk of osteoporosis. Multiple hemophilia and hemophilic arthropathy associated factors correlate with a low bone mineral density (BMD) in PWHs. The aim of this study was to assess the long-term development of BMD in PWH as well as to analyze potentially influencing factors.Methods A total of 33 adult PWHs were evaluated in a retrospective study. General medical history, specific-hemophilia-associated comorbidities, joint status using the Gilbert score, calcium level, and vitamin D level as well as at least two results of bone density measurements with a minimum range of 10 years per patient were taken into account.Results The BMD did not change significantly from one point of measurement to the other. A total of 7 (21.2%) cases of osteoporosis and 16 (48.5%) cases of osteopenia were identified. The two following significant correlations could be revealed: the higher the patients' body mass index, the higher their BMD (r = 0.41; p = 0.022). Moreover, a high Gilbert score came along with a low BMD (r = −0.546; p = 0.003).Conclusion Even if PWHs frequently suffer from a reduced BMD, our data suggest that their BMD remains constant on a low level in the course of time. A risk factor of osteoporosis often found in PWHs is a vitamin D deficiency and joint destruction. Therefore, a standardized screening of PWHs on BMD reduction by collecting vitamin D blood level and assessing joint status seems appropriate.
Keywords: hemophilia; osteoporosis; osteopenia; follow-up